Lymphatic Function in Autoimmune Diseases - Schwartz, Noa; Chalasani, Madhavi Latha S.; Li, Thomas M.; Feng, Zhonghui; Shipman, William D.; Lu, Theresa T. (Frontiers in Immunology, 2019)
Lymphatic vessels are critical for clearing fluid and inflammatory cells from inflamed tissues and also have roles in immune tolerance. Given the functional association of the lymphatics with the immune system, lymphatic dysfunction may contribute to the pathophysiology of rheumatic autoimmune diseases. Here we review the current understanding of the role of lymphatics in the autoimmune diseases rheumatoid arthritis, scleroderma, lupus, and dermatomyositis and consider the possibility that manual therapies such as massage and acupuncture may be useful in improving lymphatic function in autoimmune diseases.